2015
DOI: 10.13189/ujer.2015.030302
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coaching and Mentoring Programs to Improve Students Competencies: Case Study of Beastudi Etos Scholarship

Abstract: Progress of a country largely determined by quality of its human resources and quality of human life is much influenced by educational factors. Chains of poverty absolutely cannot be separated from economic, health and educational factors. Therefore, one effort to break chains of poverty is to provide proper education. Dompet Dhuafa through Beastudi Etos had conducting educational empowerment with provide coaching, mentoring and financial assistance for poor students. With coaching and mentoring, scholarship r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another effective strategy for being good mentors is giving feedback, as McGraw and Davis (2017) concluded from research findings that feedback, especially inquiry-oriented one, enhanced students' learning, extended and deepened understanding. Through their elaborate procedures, coaching and mentoring are believed to positively affect student learning outcomes, as exemplified by research results conducted by Udintoma and Srinovita (2015), aimed to investigate the effect of coaching and mentoring programs to improve student competencies, and found that the programs improved knowledge, skills, attitudes, and competency of scholarship recipients studying at five universities. In addition, Stahl, Sharplin, and Kehrwald (2016) conducted their research to develop pre-service teachers' confidence through real-time coaching in teacher education, and found the real-time coaching model improved the pre-service teachers' sense of confidence and ownership of learning by developing practical skills, effective attributes, and disposition toward continual improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Another effective strategy for being good mentors is giving feedback, as McGraw and Davis (2017) concluded from research findings that feedback, especially inquiry-oriented one, enhanced students' learning, extended and deepened understanding. Through their elaborate procedures, coaching and mentoring are believed to positively affect student learning outcomes, as exemplified by research results conducted by Udintoma and Srinovita (2015), aimed to investigate the effect of coaching and mentoring programs to improve student competencies, and found that the programs improved knowledge, skills, attitudes, and competency of scholarship recipients studying at five universities. In addition, Stahl, Sharplin, and Kehrwald (2016) conducted their research to develop pre-service teachers' confidence through real-time coaching in teacher education, and found the real-time coaching model improved the pre-service teachers' sense of confidence and ownership of learning by developing practical skills, effective attributes, and disposition toward continual improvement.…”
Section: Introductionmentioning
confidence: 99%